Everyday life in Viking times - Martell, Hazel (New York : F. Watts, 1994)
Discusses what everyday life was like in Viking times by using photographs of actual objects and illustrations with text.
Who were the Vikings? -- How do we know about the Vikings? -- On the farm -- Viking homes -- Around the hearth -- Eating and drinking -- Clothes and jewelry -- Viking warriors -- Transportation -- Crafts -- Buying and selling -- Viking religion -- Entertainment -- Writing and storytelling.
Includes index.
Booklist.
Library Talk.
Wilson's Children.
5.5
5-8
Keywords: Northmen -- Juvenile literature; Vikings -- Juvenile literature; Vikings; Vikings